2016
DOI: 10.1103/physrevd.94.032009
|View full text |Cite
|
Sign up to set email alerts
|

Observation ofe+eηJ/ψ

Abstract: The process e + e − → η ′ J/ψ is observed for the first time with a statistical significance of 8.6σ at center-of-mass energy √ s = 4.226 GeV and 7.3σ at √ s = 4.258 GeV using data samples collected with the BESIII detector. The Born cross sections are measured to be (3.7 ± 0.7 ± 0.3) and (3.9 ± 0.8 ± 0.3) pb at √ s = 4.226 and 4.258 GeV, respectively, where the first errors are statistical and the second systematic. Upper limits at the 90% confidence level of the Born cross sections are also reported at other… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…5 (left), which are consistent with previous Belle result [23]. The process e + e − → η ′ J/ψ was observed for the first time [24] and the measured Born cross section is shown in Fig. 5 (right) which indicates ψ(4160) → η ′ J/ψ.…”
Section: Z C (4020) and Z C (4025)supporting
confidence: 89%
“…5 (left), which are consistent with previous Belle result [23]. The process e + e − → η ′ J/ψ was observed for the first time [24] and the measured Born cross section is shown in Fig. 5 (right) which indicates ψ(4160) → η ′ J/ψ.…”
Section: Z C (4020) and Z C (4025)supporting
confidence: 89%
“…In addition, the ground state in the tetraquark picture (Esposito et al, 2015b), Y (4008), is not confirmed by the recent high-statistics data from BESIII (Ablikim et al, 2017c). Meanwhile, the cross sections for e + e − → ψ ππ (Aubert et al, 2007;Wang et al, 2007), η J/ψ (Ablikim et al, 2016b) and ηJ/ψ and 8 In this context it is interesting to note that also the hybrid picture predicts a large coupling of Y (4260) to D 1 (2420)D (Barnes et al, 1995;Close and Page, 2005;Kou and Pene, 2005), which could be interpreted as the necessity of considering D 1D as a component. π 0 J/ψ (Ablikim et al, 2015b) do not show any structure around the Y (4260) energy region.…”
Section: Y (4260) and Other Vector Statesmentioning
confidence: 94%
“…Thus the form factors of the B c meson into the light meson π 0 will only depend on a small Isospin symmetry breaking effect, which is very similar to the case where the cross sections of e + e − → J/ψη(η ) are around pb while there is no signal for e + e − → J/ψπ 0 [17,18].…”
Section: Introductionmentioning
confidence: 73%